Ответы и объяснения

  • Участник Знаний
2013-12-02T08:48:13+04:00
№11
1)1*(a-b)^2/(a-b)(a+b)(a=b)=(a-b)/(a+b)^2
2)(a-b)/a(a+b)-(a-b)/(a+b)^2=((a-b)(a+b)-a(a-b)/a(a+b)^2=(a-b)(a+b-a)/a(a+b)^2=b(a-b)/a(a+b)^2
3)b(a-b)/a(a+b)^2:(a-b)/a(a+b)=b(a-b)/a(a+b)^2*a(a+b)/(a-b)=b/a+b
№12
1)3/(x-2)^2+2/(x-2)(x+2)=(3(x+2)+2(x-2))/(x-2)^2(x+2)=(5x+2)/(x-2)^2(x+2)
2)(5x+2)/(x-2)^2(x+2)*(x-2)^2=(5x+2)/(x+2)
3)(5x+2)/(x+2)-5x/(x+2)=2/x+2
№13
1)=с*(c-2)(c+2)/(c+2)*C=c-2
2)3c-2/c+2-(c-2)-4c/c+2=(3c-2-c^2+4-4c)/c+2=-c^2-c+2/c+2=-(c+2)(c-1)/c+2=-(c-1)=1-c

-c^2-c+2=-(c^2+c-2)=-(c+2)(c-1)
c1+c2=-1,c1*c2=-2,c1=-2,c2=1
спасибо не поможешь с 13?
Комментарий удален
Комментарий удален
спасибо
Комментарий удален